2013
DOI: 10.1063/1.4773583
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and theoretical investigation of the electronic structure of Cu2O and CuO thin films on Cu(110) using x-ray photoelectron and absorption spectroscopy

Abstract: The electronic structure of Cu(2)O and CuO thin films grown on Cu(110) was characterized by X-ray photoelectron spectroscopy (XPS) and X-ray absorption spectroscopy (XAS). The various oxidation states, Cu(0), Cu(+), and Cu(2+), were unambiguously identified and characterized from their XPS and XAS spectra. We show that a clean and stoichiometric surface of CuO requires special environmental conditions to prevent loss of oxygen and contamination by background water. First-principles density functional theory XA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

28
239
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 262 publications
(267 citation statements)
references
References 67 publications
28
239
0
Order By: Relevance
“…8). These spectra match well in both peak position and line shape with previously published reports 42,43 . The Cu L-edge spectra of the Cu 2 (OH) 3 Cl precursor at open-circuit potential shows an L 3 -edge peak at 930.7 eV and an L 2 -edge peak at 950.7 eV, which matches well with CuO, clearly indicating that Cu begins in the + 2 oxidation state ( Supplementary Fig.…”
Section: Structural Characterizationsupporting
confidence: 79%
“…8). These spectra match well in both peak position and line shape with previously published reports 42,43 . The Cu L-edge spectra of the Cu 2 (OH) 3 Cl precursor at open-circuit potential shows an L 3 -edge peak at 930.7 eV and an L 2 -edge peak at 950.7 eV, which matches well with CuO, clearly indicating that Cu begins in the + 2 oxidation state ( Supplementary Fig.…”
Section: Structural Characterizationsupporting
confidence: 79%
“…Indeed, Young 228 et al and Gwathmey 229 et al found that the order of oxidation rate for the low-index surfaces is (100), (111), (110) with (100) the fastest oxidising facet, for a wide range of temperatures. Rhodin 274 found instead the order to be (100), (110), (111) with (100). This difference in ordering could be due to several factors, for example the use of very different experimental analysis techniques.…”
Section: Long-term Copper Oxidationmentioning
confidence: 99%
“…The MR reconstruction (Fig. 4c, 5b) can be viewed as a c(2 × 2) structure with each fourth [100] row of Cu atoms missing. Between 0.3 and 0.5 ML, Cu atoms are ejected from the c(2 × 2) domains 118,147 and MR islands start forming on terraces, until, at 0.5 ML coverage, a network of missing-row reconstruction islands covers the whole surface 116,133 .…”
Section: Cu(100)mentioning
confidence: 99%
“…Under an environment of CO and O 2 at elevated pressures, two new peaks develop: one peak at 531.2 eV, which is related to the formation of a small amount of hydroxy groups [15] because of an increase in the amount of background water, and a second peak at 529.1 eV, which is due to the formation of CuO. [16] The TiCuO x film with a submonolayer load of Ti (0.5 AE 0.1 ML) gives only a small CuO peak (529.1 eV), which is likely associated with regions of pure Cu 2 O, compared to the larger peak that was observed for the Cu 2 O film. The presence of titanium preserves the highly active Cu + sites on the surface and thus prevents deactivation of the catalysts.…”
mentioning
confidence: 98%